Targeting netrin‐3 in small cell lung cancer and neuroblastoma. Issue 4 (15th March 2021) - Jiang, Shan; Richaud, Mathieu; Vieugué, Pauline; Rama, Nicolas; Delcros, Jean‐Guy; Siouda, Maha; Sanada, Mitsuaki; Redavid, Anna‐Rita; Ducarouge, Benjamin; Hervieu, Maëva; Breusa, Silvia; Manceau, Ambroise; et al.
Abstract: The navigation cue netrin‐1 is well‐documented for its key role in cancer development and represents a promising therapeutic target currently under clinical investigation. Phase 1 and 2 clinical trials are ongoing with NP137, a humanized monoclonal antibody against netrin‐1. Interestingly, the epitope recognized by NP137 in netrin‐1 shares 90% homology with its counterpart in netrin‐3, the closest member to netrin‐1 in humans, for which little is known in the field of cancer. Here, we unveiled that netrin‐3 appears to be expressed specifically in human neuroblastoma (NB) and small cell lung cancer (SCLC), two subtypes of neuroectodermal/neuroendocrine lineages. Netrin‐3 and netrin‐1 expression are mutually exclusive, and the former is driven by the MYCN oncogene in NB, and the ASCL‐1 or NeuroD1 transcription factors in SCLC. Netrin‐3 expression is correlated with disease stage, aggressiveness, and overall survival in NB. Mechanistically, we confirmed the high affinity of netrin‐3 for netrin‐1 receptors and we demonstrated that netrin‐3 genetic silencing or interference using NP137, delayed tumor engraftment, and reduced tumor growth in animal models. Altogether, these data support the targeting of netrin‐3 in NB and SCLC. Synopsis: Expression and function of netrin‐3 have so far never been investigated in human cancers. Based on cohort analyses, this study shows that netrin‐3 is a putative therapeutic target in both small cell lung cancer (SCLC) and neuroblastoma (NB). Netrin‐3 expression is specific to the neuroendocrine/neuroepithelial cell lineage. Netrin‐1 and netrin‐3 are mutually exclusive in the vast majority of human cancer cell lines. Netrin‐3 expression is correlated with NB poor prognosis. MYCN, NEUROD1 and ASCL‐1 regulate transcription of netrin‐3. Netrin‐1 and netrin‐3 could be targeted by the same therapeutic monoclonal blocking antibody. Abstract : Expression and function of netrin‐3 have so far never been investigated in human cancers. Based on cohort analyses, this study shows that netrin‐3 is a putative therapeutic target in both small cell lung cancer (SCLC) and neuroblastoma (NB).